Investigation of LSM-8YSZ cathode within an all ceramic SOFC. Part I: Chemical interactions. Issue 10 (August 2020) - Harboe, S.; Sohn, Y.J.; Guillon, O.; Menzler, N.H.
Abstract: This work focuses on a novel, co-sintered, all-ceramic solid oxide fuel cell (SOFC) concept. The objective is the understanding of interaction and degradation mechanisms of the cathode and current collector layers within the design during co-sintering. Half cells consisting of silicate mechanical support, lanthanum strontium manganite (LSM) current collector, LSM mixed with 8 mol% yttria-stabilized zirconia (8YSZ) composite cathode and 8YSZ electrolyte were co-sintered at 1150 °C < T < 1250 °C. Crystallographically stable LSM compositions within the design were identified. However, the cathode and silicate/electrolyte interacted by interdiffusion of Zn (gas diffusion) and Mn (solid diffusion), and by the formation of several reaction phases (between silicate and cathode only). Introducing silicate poisoning decreased the electrochemical performance of the cell by around 40%. This is likely due to the formation of the Zn- and Mn-rich phase in the cathode, but may also be caused by a higher ohmic resistance of the current collector.